New challenges and solutions from a linguistic point of view - Reinhold, Utri (Glottodidactica, 2009)
Bilingual education has many aspects. Teachers and parents of bilingual children face many difficult issues. This article starts with the definition of the problem and gives different types of bilingualism. Elements of the language programs in school, that are to be changed resp. developed, are presented. By this semilingualism should be avoided, the integration of children of a different L 1 and their equal career chances are to be guaranteed. Some innovative and creative projects show the right way.